89.3k views
1 vote
Rewrite the equation 2 = -5x + (2y + 2x) in slope intercept form (y = mx + b or y = 5x - 4)​

User Mguijarr
by
6.1k points

2 Answers

5 votes

Start with


2=-5x+(2y+2x)

Sum like terms on the right hand side:


2=-3x+2y

Add 3x to both sides:


3x+2=2y

Divide both sides by 2:


(3)/(2)x+1=y

Which is the required form: reading the equality from right to left gives


y=(3)/(2)x+1

User Docuemada
by
6.4k points
3 votes
See picture for answer :::
Rewrite the equation 2 = -5x + (2y + 2x) in slope intercept form (y = mx + b or y-example-1
User Alexander Lubyagin
by
6.3k points